2023
DOI: 10.1108/er-03-2022-0152
|View full text |Cite
|
Sign up to set email alerts
|

Smart working as an organisational process or as a social change? An Italian pandemic experience

Abstract: PurposeAlong the coronavirus pandemic, huge business challenges are facing as a result of collapsing customer demand and organisational significant changes supported by digital development, while the increasing social and environmental needs involve business and individuals. The authors argue that this trend is modifying organisational and market logic, replacing them with values and practices linked to community-based models. The present work aims to study the impact that smart working (SW) has on the worker,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Finally, while experts often advocate that the introduction of telework is paired with disruptive managerial practices, empirical evidence suggests caution in introducing new control principles in stark conflict with the prevailing conventions, as they may trigger resistance and lead to adoption failure (Taskin & Edwards, 2007). The studies conducted during the pandemic unveil, through procedural analysis, how tacit and hidden practices of managerial control evolve (Hartner-Tiefenthaler et al, 2021), how civil servants reconceptualize workspaces, redefine time and emotions (Morea et al, 2023), and end up employing different heuristics. For example, social caseworkers' reliance on physical cues is offset by documentary analysis (Flügge & Møller, 2023).…”
Section: The Dynamics Of Teleworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while experts often advocate that the introduction of telework is paired with disruptive managerial practices, empirical evidence suggests caution in introducing new control principles in stark conflict with the prevailing conventions, as they may trigger resistance and lead to adoption failure (Taskin & Edwards, 2007). The studies conducted during the pandemic unveil, through procedural analysis, how tacit and hidden practices of managerial control evolve (Hartner-Tiefenthaler et al, 2021), how civil servants reconceptualize workspaces, redefine time and emotions (Morea et al, 2023), and end up employing different heuristics. For example, social caseworkers' reliance on physical cues is offset by documentary analysis (Flügge & Møller, 2023).…”
Section: The Dynamics Of Teleworkmentioning
confidence: 99%
“…Work-life balance 9 Chinyamurindi, 2022;de Velasco et al, 2023;Lopes Junior & Daniel, 2022;Morea et al, 2023;Todisco et al, 2023;Williamson et al, 2023) 3 Williamson et al, 2023) Self-reported individual productivity 5 (Chow et al, 2022;da Silva & da Rosa, 2022;de Velasco et al, 2023;Williamson et al, 2023) 2 (da Silva & da Rosa, 2022; ) 4 (Kahn et al, 2022Varotsis et al, 2022;Williamson et al, 2023) Resilience 6 Mayers et al, 2023;Ridde et al, 2022;Rivera Macias & Casselden, 2022;Todisco et al, 2023) Affective Job satisfaction 2 Sociability 2 (Cellini et al, 2021;Rivera Macias et al, 2022) Travel costs 2 (Cellini et al, 2021;Todisco et al, 2023) Turnover intentions 2 (Leider et al, 2023, Lewis et al, 2023 Note: A complete list of references is available online in the Harvard Dataverse, at the link provided in the data availability statement.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The workload, particularly associated with technologies, has led to stress and, in turn, undermined organizational effectiveness and employees’ well-being ( Pace et al, 2021 ; Nguyen and Tuan, 2022 ). Morea et al (2023) showed that these professionals were able to redefine space, time, organizational involvement, and a better work-life balance during the pandemic. Nevertheless, during this time, the widespread use of remote work in the public sector raised concerns about the impact on workers’ well-being ( Marino and Capone, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this transition has introduced new challenges, including social isolation, difficulties in disconnecting, unsuitable tools for meeting objectives, enforced cohabitation, and diminished organizational support, which also encompasses communication challenges with supervisors and colleagues [17]. Furthermore, it has upset the balance between work and personal life [18][19][20][21][22] and led to increased interruptions [23], particularly at home, thereby undermining wellbeing in the workplace [18,24]. While the dichotomous impact of smart working has been recognized, the literature on the subject is still scarce.…”
Section: Introductionmentioning
confidence: 99%